Muscle size, quality, and body composition: Characteristics of Division I cross-country runners - Roelofs, E. J.; Smith-Ryan, A. E.; Melvin, M. N.; Wingfield, H. L.; Trexler, E. T.; Walker, N. (The Journal of Strength and Conditioning Research, 2015)
The primary purpose of this study was to identify the relationship between muscle cross-sectional area (mCSA), echo intensity (EI), and body composition of Division I cross-country runners. The secondary purpose was to examine differences in these variables in athletes stratified based on stress-fracture (SFx) history. Thirty-six athletes were stratified based on sex and SFx history. A panoramic scan vastus lateralis was performed using a GE Logiq-e B-mode ultrasound. Echo intensity and mCSA were determined from the scan using a grayscale imaging software (ImageJ). Body composition measures were determined using dual-energy x-ray absorptiometry. For females, mCSA was significantly correlated with left leg lean mass (LM; R = 0.54) and EI (R = -0.57). Lean mass was significantly correlated with bone mineral density (BMD; R = 0.58) and bone mineral content (BMC; R = 0.56), whereas BMC was also correlated with leg LM (R = 0.72). For males, mCSA was significantly correlated with leg LM (R = 0.66), BMD (R = 0.50), and BMC (R = 0.54). Leg LM was significantly correlated with BMD (R = 0.53) and BMC (R = 0.77). Personal best times for males were significantly correlated with fat mass (R = 0.489) and %fat (R = 0.556) for the 10- and 5-km races, respectively. Female and male athletes with a history of SFx were not significantly different across any variables when compared with athletes with no history. These correlations suggest that more muscle mass may associate with higher BMD and BMC for stronger bone structure. Modifications in training strategies to include heavy resistance training and plyometrics may be advantageous for preventing risk factors associated with SFx reoccurrence.